Integrated multi-omics reveals cellular and molecular interactions governing the invasive niche of basal cell carcinoma - Laura Yerly; Christine Pich-Bavastro; Jeremy Di Domizio; Tania Wyss; Stéphanie Tissot-Renaud; Michael Cangkrama; Michel Gilliet; Sabine Werner; François Kuonen (Nature Communications, 2022)
The role of reciprocal tumour-stroma interactions in tumour invasion remains poorly characterised. Here, single-cell and spatial transcriptomics identifies the cell populations and their transcriptional reprogramming contributing to the spatial organization of the basal cell carcinoma invasive niche.